The European Union’s Energy Policy From the Perspective of a Central-Eastern European Country: Romania - Szendrei, Tamás (Maastricht 30: A Central European Perspective, 2025)
This scientific article examines the European Union’s (EU) energy policy from the perspective of Romania, focusing on its unique position as a Central-Eastern European country. Against the backdrop of the 30-year anniversary of the Maastricht Treaty, the relevance and challenges of EU energy policy are explored in relation to Romania’s energy landscape. The article analyses the current legislation, including the European Energy Charter Treaty1, as well as the Energy Union initiative, which aims to improve energy efficiency, reduce import dependence, and stimulate economic growth. Additionally, it investigates the implications of the energy crisis triggered by the Russian–Ukrainian war on defining the “energy mix” and the extent of the EU’s influence versus Member States’ autonomy. The concept of solidarity, particularly regarding compulsory gas sharing, is examined through the lens of Western European, Central and Eastern European, and candidate countries, addressing the reasons behind sharing energy stocks. Furthermore, the article evaluates the contribution of Regulation (EU) 2022/869 and projects identified under Trans-European Networks to enhancing security of supply in the countries under review. Ultimately, this article offers insights into the complexities, challenges, and opportunities faced by Romania and the wider EU in shaping energy policies that promote sustainability, security, and cooperation. Keywords: European Union Energy Policy, Romania Energy Perspective, Energy Security in the EU, Sustainable Energy Strategies, Energy Market Liberalization, Energy Diversification Strategies, Renewable Energy Targets, Romanian Electricity Sector, Nuclear Power in Romania, Hydro, Solar and Wind Energy in Romania, IPO, Energy Transmission Infrastructure, Energy Sustainability in EU, Security of Energy Supply